Assessment on the ageing of sandwich composites with vinylester-based composite faces and PVC foam core in various harsh environments. (1st April 2019) - Ding, Anxin; Wang, Jihui; Ni, Aiqing; Li, Shuxin
Abstract: The behaviour of moisture absorption and evolution of various mechanical properties for the sandwich composites immersed into two humid conditions: seawater with 30 °C (SWL) and purewater with 80 °C (PWH) have been examined by Ding et al. (2018). In this paper, three relatively harsh environmental conditions: salt-fog spray ageing (SFS), hygrothermal atmosphere alternating high low temperature (HHL) and solar radiation in combination with water vapour (SRW) are determined. Further studies on the ageing behaviour of previously selected sandwich composites constituted of thick ECR glass fibre reinforced vinylester composite faces bonded to closed-cell PVC were carried out under aggression of newly added three artificial environmental conditions. To this end, the specimens were prepared by VIMP and then exposed to the new three conditions for 1008 h. The moisture uptake before desiccation and after desiccation as well as various mechanical properties, including flatwise tension strength, flatwise compressive strength, in-plane shear strength, shear strength using short beam bending and edgewise compressive strength, were measured and compared with previous data from SWL and PWH. The weight change indicates that the specimens exposed to newly added environmental conditions absorb much less moisture and chemically bound water, meanwhile the mechanical characterization reveals that specimens exposed to the SRW deteriorate significantly in the faces-core interfacial properties.